PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN - Adika Bayu Priatno; Prita Andini (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the impact of Profitability, Leverage, Firm Size and Liquidity on Tax Avoidance. In this study, Profitability is proxied by Return on Assets (ROA), Leverage is proxied by Debt Equity Ratio (DER), Firm Size is proxied by Total Assets, and Liquidity is proxied by Current Ratio (CR). The population in this study are automotive and component manufacturing companies. Data collection uses purposive sampling method and based on predetermined criteria, the number of samples obtained is 12 automotive and component manufacturing companies during the 2017-2020 period. The data analysis technique used is multiple linear regression analysis. The results showed that Profitability, Liquidity and Firm Size had no impact on Tax Avoidance, while Leverage has a positive impact on Tax Avoidance.